2005
DOI: 10.1017/s0952523805226032
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal cells in the retina of a diurnal rodent, the agouti (Dasyprocta aguti)

Abstract: The morphology and distribution of normally placed and displaced A horizontal cells were studied in the retina of a diurnal hystricomorph rodent, the agouti Dasyprocta aguti. Cells were labeled with anti-calbindin immunocytochemistry. Dendritic-field size reaches a minimum in the visual streak, of about 9,000 microm(2), and increases toward the retinal periphery both in the dorsal and ventral regions. There is a dorsoventral asymmetry, with dorsal cells being larger than ventral cells at equal distances from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Other neurons of the retinal ganglion cell layer comprised displaced amacrine cells and displaced horizontal cells, the later relatively rare in comparison with the former [42] [44] . Displaced amacrine cells had small cell bodies, dark staining nuclei, rarely visible nucleoli, and scant cytoplasm.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other neurons of the retinal ganglion cell layer comprised displaced amacrine cells and displaced horizontal cells, the later relatively rare in comparison with the former [42] [44] . Displaced amacrine cells had small cell bodies, dark staining nuclei, rarely visible nucleoli, and scant cytoplasm.…”
Section: Resultsmentioning
confidence: 96%
“…Ganglion cells comprise a heterogeneous population of neurons readily distinguishable from other neurons (thin arrows), glial cells (thick arrows), and endothelial cells. The non-ganglion cell neurons of the retinal ganglion cell layer comprise displaced amacrine cells and displaced horizontal cells, the later relatively rare in comparison with the former [42] [44] . The glial cells comprise microglia (thick arrow in B ) and astrocytes (thick arrow in D ), which are generally located internally (microglia) or externally (astrocytes and microglia) to the retinal ganglion cells.…”
Section: Resultsmentioning
confidence: 99%
“…Silveira et al (1989) evaluated the distribution of retinal ganglion cells and found a well-developed visual streak, a nasotemporal band of high ganglion cell density located about 2–3 mm dorsal to the optic disk, and a dorsoventral asymmetry in ganglion cell topography. A recent paper described the retinal topography of A-type horizontal cells using immunocytochemistry (de Lima et al, 2005). Interestingly, the density of this cell type that exclusively connects to cones also showed a dorsoventral asymmetry with respect to dendritic field size.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we used immunocytochemistry with cone opsin–specific antibodies to study the retinal topography and mosaic regularity of cone photoreceptors of the agouti ( Dasyprocta aguti ), a hystricomorph rodent of large body size displaying a predominantly diurnal, visually guided behavior. The agouti’s visual system has been the subject of several studies concerning eye optics (Oswaldo-Cruz et al, 1985), horizontal cell morphology and density (de Lima et al, 2005), ganglion cell morphology and density (Silveira et al, 1989; Gomes et al, 1998), and visual cortex morphology and physiology (Picanço-Diniz et al, 1989, 1991, 1992; Costa et al, 1996; Elston et al, 2006). Part of the present results have previously been presented in abstract form (de Lima et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Data sets Three horizontal cell fields were analysed: fields A and B are from macaque (A: unpublished data; B: Figure 7 of Wässle et al (2000)); field C is from cat ( Figure 12 of ). To keep our notation concise (rather than claiming any equivalence of neuronal types across species), we denote type B cat horizontal cells as "type 1", and type A horizontal cells as "type 2", in line with previously-noted similarities of primate H1 and other mammalian B cells (de Lima et al, 2005). Fields were digitised, and the cell location taken to be the centre of each soma.…”
Section: Methodsmentioning
confidence: 99%